The health system costs of post abortion care in Tanzania - Naomi Lince-Deroche; George Ruhago; Philicia W. Castillo; Patrice Williams; Projestine Muganyizi; Akinrinola Bankole (BMC, 2021)
Abstract Background Unsafe abortion is common in Tanzania. Currently, postabortion care (PAC) is legally provided, but there is little information on the national cost. We estimated the health system costs of offering PAC in Tanzania in 2018, at existing levels of care and when hypothetically expanded to meet all need. Methods We employed a bottom-up costing methodology. Between October 2018 and February 2019, face-to-face interviews were conducted with facility administrators and PAC providers in a sample of 40 health facilities located across seven mainland regions and Zanzibar. We collected data on the direct and indirect cost of care, fees charged to patients, and costs incurred by patients for PAC supplies. Sensitivity analysis was used to explore the impact of uncertainty in the analysis. Results Overall, 3850 women received PAC at the study facilities in 2018. At the national level, 77,814 women received PAC, and the cost per patient was $58. The national health system cost for PAC provision at current levels totaled nearly $4.5 million. Meeting all need for PAC would increase costs to over $11 million. Public facilities bore the majority of PAC costs, and facilities recovered just 1% of costs through charges to patients. On average PAC patients incurred $7 in costs ($6.17 for fees plus $1.35 in supplies). Conclusions Resources for health care are limited. While working to scale up access to PAC services to meet women's needs, Tanzanian policymakers should consider increasing access to contraception to prevent unintended pregnancies.